A systematic revision of Neotropical lizards in the clade Hoplocercinae (Squamata: Iguania) - Torres-Carvajal, Omar; Etheridge, Richard; de Queiroz, Kevin (Zootaxa, 2011)
The clade Hoplocercinae includes 13 species assigned to three taxa traditionally ranked as genera—Enyalioides, Hoplocercus, and Morunasaurus—, and distributed on both sides of the Andes from Panama to Brazil. We provide a revised taxonomy of Hoplocercinae including synonymies, diagnoses, standardized descriptions, distributions, notes on color and natural history, and a key for species identification. We also propose vernacular names in English and Spanish for all species.